Integrative approach resolves the taxonomy of the Ozothamnus ledifolius (Asteraceae: Gnaphaliae) species complex in Tasmania, Australia - de Salas, Miguel F.; Schmidt-Lebuhn, Alexander N. (Phytotaxa, 2018)
Close examination of specimens of the Ozothamnus ledifolius species complex (O. ledifolius, O. ericifolius and O. purpurascens) collected throughout Tasmania, Australia, revealed the existence of more taxa than hitherto recognised. An integrative approach employing morphological, genotyping and environmental data of specimens resolved the complex, and showed good support for O. ledifolius and O. ericifolius as currently circumscribed, further clarifying the existence of four additional, distinct taxa: Ozothamnus purpurascens, with revised and clarified typification; O. reflexus comb. & stat. nov., a taxon to which the name O. purpurascens was previously misapplied; O. buchananii spec. nov., a novel taxon from mid–high elevations in north-eastern Tasmania; and O. floribundus spec. nov., a rare and highly localised novel taxon in lowland south-eastern Tasmania.